Active composite starch films containing green synthetized silver nanoparticles. (September 2017) - Ortega, Florencia; Giannuzzi, Leda; Arce, Valeria B.; García, M. Alejandra
Abstract: The aims of this work were to couple both the silver nanoparticles (AgNPs) synthesis, and filmogenic suspensions preparation, to characterize the obtained AgNPs and the derived nanocomposite films studying their antimicrobial capacity and developing an active packaging. One of the new approaches to this work is the use of low concentrations of AgNPs at which no adverse cytotoxic effects have been observed. Nanoparticles were characterized by spectrophotometric techniques and electron microscopy, finding that they are spherical with diameters varying between 5 and 20 nm and detecting the formation of agglomerates. The addition of AgNPs did not affect the filmogenic capacity of gelatinized starch suspension. The content of AgNPs caused a slight increase in film thickness and opacity, keeping the material UV-barrier capacity. A decrease in water vapor permeability with increasing AgNPs concentration was observed. Besides, AgNPs allow the matrix reinforcement, developing a more resistant and tough material, with smooth and homogeneous surfaces, as evidenced by SEM, and maintaining their heat sealing capacity. Nanocomposite films containing AgNPs concentrations greater than 71.5 ppm inhibited the growth of E. coli ATCC and Salmonella spp., which are responsible for most foodborne diseases. However, films containing 143 ppm AgNPs were selected since they better maintained their integrity to microbial attack. These active films were able to extend the shelf-life of fresh cheese samples for 21 days. Thus, it was possible to develop and characterize nanocomposite films based on corn starch and containing AgNPs, which confers them antimicrobial properties. Graphical abstract: Highlights: Active composite starch films with silver nanoparticles (AgNPs) were developed. AgNPs green synthesis and film preparation were successfully coupled. AgNPs inclusion allows the matrix reinforcement, developing a more resistant material. Nanocomposite films exhibited antimicrobial capacity. Nanocomposite films extended the shelf-life of fresh cheese samples for 21 days.